Peanut meal-derived bioactive compounds: Extraction, co-extrusion encapsulation and neuroprotection against aluminum-induced Alzheimer's disease via in silico and in vivo studies - Rasha S. Mohamed; Karem Fouda; Ahmed Salama; Engy M. Akl (Elsevier, 2024)
Background: Peanut meal (seeds waste with the red skin) contains antioxidants and anti-inflammatory compounds, which protect cells from oxidative stress and inflammation. Hypothesis: This byproduct can be used to produce nutraceutical and functional food items that may become popular. Methods: Ultrasound-assisted extraction was used to prepare peanut meal extracts at various times and with different solvents of 90 % (acetone, ethanol, methanol, and acetic acid ethyl ester). Acetone peanut meal extracting (for 20 min ) demonstrated the highest total phenolic content (83.78 mg GAE/g meal) and DPPH scavenging activity (95.83 %). Acetone peanut meal extract (PME) was analyzed by HPLC and encapsulated using sodium alginate via the co-extrusion technique. The alginate/PME microbeads were studied for their morphology and release of phenolic compounds. Results: The results of the molecular docking demonstrated a strong binding affinity, implying that the identified compounds in PME may inhibit acetylcholinesterase. Through the in vivo study, it was revealed that PME and PME microbeads demonstrated antioxidant and anti-inflammatory effects in AlCl3-treated rats. Additionally, PME and PME microbeads reduced the acetylcholinesterase activity while elevating the levels of dopamine and serotonin compared to the AlCl3-treated rats. Conclusion: This work provided valuable contributions towards the valorization of peanut byproducts, highlighting their potential neuroprotective effect against aluminum-induced Alzheimer's disease.